Adaptation and Negotiation of Muslims within the Local Catholic Community in Eastern Indonesia - Widyawati, Fransiska; Lon, Yohanes S. (Journal of Al-Tamaddun, 2023)
Muslims are a minority group in Manggarai, Flores, East Nusa Tenggara. They live alongside the Catholics who make up the majority of the population. The Catholics are known to have a strong sense of tradition in addition to their faith. The tradition is centered around rituals involving sacrificial animals and food deemed haram in Islam. As a result, Muslims are faced with a challenge that hinders their practice of the halal lifestyle. They are compelled to find ways of adaptation and negotiation, through which they can practice their faith while living in harmony and integrated with the Manggarai community. This study explores some common models which have been adopted by Muslims in Manggarai to adapt and negotiate their standing in society and factors that influence such behaviors. This ethnographic study found various working models of adaptation and negotiation that enable Muslim minorities to integrate into society while maintaining their halal lifestyle. The models depend on many factors such as cultural background, interpersonal relationship, place and time, bargaining power, personal preference, peer pressure, mindset, and interpretation of the sacred text. This study argues that the Muslim minority in Manggarai applies the non-monolithic nature of Islam. The practice of a halal lifestyle in Islam is not only a religious matter but also a socio, economic, and political one.